Performance characteristics of Indian hearing aids - Pandalay SPS; Murthy SS (Journal of All India Institute of Speech and Hearing, 1972)
Hearing aid is a miniaturised amplifier circuit, though it takes many forms, isdesigned specifically for improving human hearing. Reduction in size, improvementin acoustic quality and inconspicuousness to wear, than ever thought possible, haveresulted, in greater acceptance of these hearing aids. Hearing Aids are made asglasses, as barrettes, for behind the ear use and for use directly on the ear, as well asin the form of conventional body hearing aid